2008
DOI: 10.1007/s10753-008-9067-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Infliximab, an Anti-TNF-α Agent, on Carbon Tetrachloride-Induced Hepatic Fibrosis

Abstract: To assess the effect of infliximab, an anti-tumor necrosis factor (TNF)-alpha agent, on the carbon tetrachloride (CCl(4))-induced hepatic fibrosis in rats. Rats were randomized into three groups (n=9). The control group received only intraperitoneal (i.p.) olive oil. Hepatic fibrosis was induced by repeated i.p. injections of 1.5 ml/kg CCl(4) (1:3 mixture with olive oil) for 5 weeks in the remaining two groups which were also injected subcutaneous saline or 2 mg/kg infliximab. Infliximab reduced the levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 33 publications
2
56
0
Order By: Relevance
“…CCl4 application was carried out intraperitoneally twice per week for four weeks at 1.5 mL/kg live weight injected together with olive oil at 1:3 ratio (Bahcecioglu et al, 2008;Shaker et al, 2010).…”
Section: Ccl4 Applicationmentioning
confidence: 99%
“…CCl4 application was carried out intraperitoneally twice per week for four weeks at 1.5 mL/kg live weight injected together with olive oil at 1:3 ratio (Bahcecioglu et al, 2008;Shaker et al, 2010).…”
Section: Ccl4 Applicationmentioning
confidence: 99%
“…Because both IL-6 and TNF-α have pleiotropic effects on hepatic leukocytes in liver fibrosis (10,11), we postulated that DCs may be a central determinant of the inflammatory milieu in the fibrotic liver. To test this hypothesis, NPCs were harvested from normal and fibrotic livers and cultured for 24 hours without exogenous stimulation in parallel with NPCs from fibrotic livers that had been depleted of DCs.…”
Section: Introductionmentioning
confidence: 99%
“…When the treatment was changed with ETN or ADA, hepatotoxicity disappeared in some patients who received IFX previously [33,34]. On the other hand, TNFα blockage was associated with the hepatoprotective effect in some conditions in mice models [35,36]. Another study reported that IFX treatment can control chronic hepatitis C infections by promoting apoptotic cells and preventing liver regeneration in a transgenic mouse model [37].…”
Section: Discussionmentioning
confidence: 99%